Comparison of tensile properties data analyzed using anova and manova methods: case study data of pva-gambir blend film - Handayani, Vitri Aprilla; Railis, Razan Muhammad; Sunarsono, Hery; Azzahra, Nabila; Iby, Ilham Chayri; Abral, Hairul; Rushdan, Ahmad Ilyas; Salit, Mohd Sapuan; Azka, Muhammad Adlan (Universiti Putra Malaysia Press, 2025)
In our previous research, the Analysis of Variance (ANOVA) method was applied to analyze data on the tensile properties of pure PVA films and blend films mixing PVA (10%), BA (0.5%), and UG (1%). The results using ANOVA analysis are not significant for treatments in samples. This study compares data from Multivariate Analysis of Variance (MANOVA) and ANOVA methods. The accuracy level of both methods is α = 5% (0.05). The result showed that the tensile properties of samples using MANOVA display a significant data effect. Therefore, we recommended MANOVA because the tests were performed simultaneously.